Human Resource Influence in Small and Medium Enterprises (SMEs) and Economic Development: A Study of Some Selected Businesses in Kumo, Gombe State - Mohammed, Usman; Lamido Umar, El-haroun (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Small and Medium Enterprises (SMEs) are proved to be the key tools for developing any given economy. Economy can progress toward employment generation, increase in Gross Domestic Product (GDP), increase in the national tax and revenue with the aid of major roles played by SMEs. This signifies that human resource involvement in SMEs in any given economy played crucial roles. Therefore, this paper tends to give a theoretical exposition of Human resource involvement in SMEs and economic development with reference to some selected businesses in Kumo, Akko local government of Gombe State, Nigeria. The paper relies on both primary and secondary sources of data for review and findings. The findings of the paper indicated that human resource involvement in SMEs; Bakeries, Sachet water firms, Groundnut cakes (Kuli-Kuli) makers and E-commerce played significant roles toward economic development with reference to Kumo town, Akko local government of Gombe state, Nigeria. The paper recommended effective and efficient management of these businesses for improved development in Kumo, Gombe state and Nigeria at large. It further recommended that more of such businesses should be encouraged as well as other business opportunities that were not practiced in the local government like; shoe making, leather producing, and many others should be strategically analysed and initiated. The paper attempts to add to the knowledge domain on SMEs especially as it relates to geographical location.